GERAKAN MENABUNG SEJAK DINI MELALUI EDUKASI DAN PRAKTEK CELENGAN DI LEMBAGA PENDIDIKAN DESA SIMONGAGROK - Dewi Rohmawat Putri; Tatik Raisawati; Fara Nur Faza; Dinda Dwi Nur Saadah (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
The community service program titled "Early Saving Movement through Education and Celengan Practice at Educational Institutions in Simongagrok Village" was implemented at SDN 1 Simongagrok (23 students in grades IV–VI) and MI Tarbiyatul Athfal (20 students in grade V) to enhance early childhood financial literacy. Utilizing a blended learning approach—PowerPoint presentations, animated videos, interactive discussions, and celengan decoration practice—this activity aimed to provide understanding of saving concepts/benefits, distinguish between needs and wants, and foster habits of regularly setting aside pocket money. Results showed high student enthusiasm (80–90% active participation), improved understanding up to 75–85% (pre-post observation), and increased saving motivation through personalized celengan, although challenges with specific saving goals persist. The novelty lies in integrating periodic evaluations and personal targets, aligned with similar community service programs (2022–2025) reporting 74–96% improvements. Recommendations include teacher monitoring and curriculum integration for sustainability. The program contributes to character education in frugality and financial discipline in rural contexts.